HUBUNGAN BODY IMAGE DENGAN STATUS GIZI PADA REMAJA DI DESA KEMA II - Ivanna Manoppo; Merfin Feren Lang (Fakultas Ilmu Keperawatan Universitas Klabat, 2022)
Adolescents are a group that is vulnerable to nutritional problems. One of the physiological needs that must be met by each individual is nutritional status. The balance of nutritional intake and nutritional needs is very important in achieving optimal health. One of the factors that influence nutritional status is body image. This study aims to determine the significant relationship between body image and nutritional status in adolescents in Kema II Village. Correlation descriptive research design with a cross-sectional approach. The sampling method used is purposive sampling. The sample in the study amounted to 81 people, the data were collected using a questionnaire and measuring instruments microtoise and digital scales. The results: the description of the nutritional status of the majority of adolescents is in the normal category, namely 64 respondents (79.0%), the majority of adolescent body image images are in the moderate category, namely 60 respondents (74.1%), a significant relationship between body image and nutritional status in adolescents in Kema II Village with p value = 0.015 <0.05 and r value = - 0.269 which means it has a weak relationship with a negative relationship direction. Recommendation: This research is aimed at adolescents in order to maintain nutritional status in the normal category and maintain a positive body image and also for future researchers to be able to conduct more specific research on gender (male and female) and can examine other factors such as physical activity. .